Perception of People Living With HIV/AIDS Affecting Lost to Follow-Up of ARV Therapy - Lilik Manowati; Purwaningsih Purwaningsih; Abu Bakar (Critical Medical and Surgical Nursing Journal (CMSNJ), 2019)
ABSTRACTIntroduction: HIV/AIDS sufferers must consume antiretrovirals every day and control routinely each month to take ARVs in the hospital. The condition make patients having a risk of lost to follow up attitude. The purpose of this study was to determine the factors related to the attitude of lost to follow-up on people living with hiv/aids with arv therapy at rsud dr. soetomo surabaya. Method: This study used descriptive correlation design with a cross-sectional approach. The population were 135 patients and 100 patients were required as research participant with consequtive sampling. Independent variables were perceived susceptibility, perceived severity, perceived barrier to action, perceived benefits of action, cues to action, and self efficacy. The dependent variable was lost to follow up behavior. Data were obtained by questionnaire and analyzed with Spearman's Rho. Result: There was a relationship between perceived susceptability (p=0.002), perceived severity (p=0.025), perceived barrier to action (p=0.022) and cues to action (p=0.011) with lost to follow-up behavior. There was no correlation between perceived benefit of action (p=0.196) and self efficacy (p=0.071) with lost to follow-up behavior. Discussion: Knowledge and awareness regarding the importance taking antiretroviral drugs regularly and control routinely needs to be increased for patients with antiretroviral drugs. Further researchers are advised to conduct in-depth research (qualitative research) related to the causes of lost to follow-up behaviour thus.